2D Dual‐Metal Zeolitic‐Imidazolate‐Framework‐(ZIF)‐Derived Bifunctional Air Electrodes with Ultrahigh Electrochemical Properties for Rechargeable Zinc–Air Batteries. (4th December 2017) - Wang, Tingting; Kou, Zongkui; Mu, Shichun; Liu, Jingping; He, Daping; Amiinu, Ibrahim Saana; Meng, Wen; Zhou, Kui; Luo, Zhixiong; Chaemchuen, Somboon; Verpoort, Francis
Abstract: Here first a 2D dual‐metal (Co/Zn) and leaf‐like zeolitic imidazolate framework (ZIF‐L)‐pyrolysis approach is reported for the low‐cost and facile preparation of Co nanoparticles encapsulated into nitrogen‐doped carbon nanotubes (Co‐N‐CNTs). Importantly, the reasonable Co/Zn molar ratio in the ZIF‐L is the key to the emergence of the encapsulated microstructure. Specifically, high‐dispersed cobalt nanoparticles are fully encapsulated in the tips of N‐CNTs, leading to the full formation of highly active Co–N–C moieties for oxygen reduction and evolution reactions (ORR and OER). As a result, the obtained Co‐N‐CNTs present superior electrocatalytic activity and stability toward ORR and OER over the commercial Pt/C and IrO2 as well as most reported metal‐organic‐framework‐derived catalysts, respectively. Remarkably, as bifunctional air electrodes of the Zn–air battery, it also shows extraordinary charge–discharge performance. The present concept will provide a guideline for screening novel 2D metal‐organic frameworks as precursors to synthesize advanced multifunctional nanomaterials for cross‐cutting applications. Abstract : 2D dual‐metal zeolitic imidazolate framework with leaf‐like microstructure is rationally chosen as material platform for the facile fabrication of high‐dispersed cobalt nanoparticles encapsulated into nitrogen‐doped carbon nanotubes as bifunctional air electrodes for a high‐performance rechargeable zinc–air battery.